Pengembangan Media Pembelajaran Tematik Berbasis Powerpoint Animasi untuk Kelas V SDIT Al Mumtaz Pontianak - Eka Rindayani; Kartono Kartono; Suparjan Suparjan; Hamdani Hamdani; Asmayani Asmayani (ISLAMIKA, 2023)
This study aims to produce a product in the form of animated PowerPoint-based learning media and analyze the feasibility level of animated PowerPoint-based learning media to help learning activities on theme 1 sub-theme 1 grade V elementary school measured from the design and material aspects. This study employed qualitative and quantitative approach. The technique of data analysis used the method of development which known as Research and Development (R&D). With 4D stages: define, design, development, and dessiminite. This study was validated by 2 experts and 30 students were get involved as respondents who were divided into 2 groups, namely a small group of 9 people and a large group of 21 people.The results of this study revealed that the development of animation powerpoint-based learning media measured from the design aspect and the material aspect is stated to be very feasible as a learning medium to assist learning activities on theme 1 sub-theme 1 grade V elementary school with a feasibility presentation value of 94.76% and 96.83% of the trial activities were included in the “Very Good” category, supported by the feasibility results of the expert validators with a feasibility value of 97.58% and 96.11%, which were included in the “Very valid” category, respectively.